Impact of Student Factors on Hybrid Learning Performance Across Educational Levels: An Empirical Study - Lanny; Yoseph Budi; Wanda Gema P.A. Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2024)
COVID-19 has brought many changes in all aspects of our lives, especially in education. We shifted from traditional face-to-face learning to online learning and finally to hybrid learning. With the combination of face-to-face learning and online learning, hybrid learning acts as the best solution to accommodate the best teaching-learning activities. This study investigates the effects of students’ motivation to learn, social interaction, teacher-student communication and technology readiness of Junior and Senior High students during the hybrid learning. This study was conducted using a quantitative method by analyzing the data collected from an online questionnaire distributed to 403 respondents. The analysis model used in this research is structural equation modeling (SEM-PLS) with data processing tools with Smart PLS 4. The results showed that there was a positive and significant effect between students’ motivation to learn, social interaction, teacher-student communication and technology readiness towards learning performance during hybrid learning. As for the results of the moderating effect of level of education, there was no significant difference between students’ motivation to learn and technology readiness towards learning performance between Junior High and Senior High students, but there was a significant difference between social interaction and teacher-student communication towards learning performance between Junior High and Senior High students. Further research should be conducted to investigate the impact of these variables on learning performance using different methods such as PLS-MGA, qualitative methods, or mixed methods.